Processo de adaptação de próteses auditivas em usuários atendidos em uma instituição pública federal: parte II: resultados dos questionários de auto-avaliação - Freitas, Carine Dias De (2007)
An efficient rehabilitation must be able to reduce impairment effects over the auditory and communication skills of individuals and promote psychosocial well being. AIMS: check the feasibility of using self-assessment questionnaires and compare the results achieved by hearing aid fitting in users from a federal public institution, with and without complaints related to hearing amplification characteristics. MATERIALS AND METHODS: 25 individuals, from 13 to 77 years of age, users of hearing aids. The HHIE-S/HHIA (Hearing Handicap Inventory for the Elderly Screening Version or for Adult) and APHAB (Abbreviated Profile of Hearing Aid Benefit) self-assessment questionnaires used with individuals without (Group 1) and with complaints related to amplification characteristics (Group 2). RESULTS: we did not find significant differences between the HHIE-S/HHIA and APHAB groups; except in APHAB s ease of communication item, where Group 1 seemed to benefit more. Moreover, we noticed a significant reduction in hearing disability with the use of hearing aids in favorable communication situations, noisy environments for both groups. CONCLUSION: these questionnaires proved to be valuable for predicting the difficulties faced by the users, and significant differences were found in favorable communication situations, where the group without complaints had the most benefit.